OPTIMIZATION OF KERATIN DECOMPOSITION BY CHRYSOSPORIUM TROPICUM - FIRDOS KATIAR; R.K.S.KUSHWAHA (International Journal of Pharma and Bio Sciences, 2013)
The loss in weight of keratin substances, pH change and protein released into the culture medium provide definite evidence of the proteolytic and keratin decomposing ability of C. tropicum GPCK 511 and C. tropicum GPCK 512. However, the results showed that more protein released and more weight loss was found in shaking condition in comparison to static condition. From the results it is clear that maximum values of protein and weight loss were mostly obtained at 10 to 15 days indicating optimum incubation at this period.